(untitled) (LEARNing Landscapes, 2013)
Including families is an important theme in the early childhood classroom. Teachers, however, report feeling unprepared when a child’s family is composed of same-sex parents. Gay and lesbian families, in turn, feel invisible, silenced, and excluded. Overall, the topic is rarely covered in teacher education programs—in response, an online course on gay and lesbian families was developed. Teachers assessed the knowledge conveyed, comfort with the content, and helpfulness of the tools provided. The findings confirmed that most teachers had received no pre-service or professional development training on the topic. The majority wanted training that included tools for being inclusive and welcoming.